LITERATURE REVIEW: MENGKONSUMSI JUNK FOOD DAN KEJADIAN OBESITAS PADA REMAJA SMA - Siti Paramesthi Sani; Lina Handayani (Dian Nuswantoro Semarang, 2021)
Consuming junk food has become a habit in adolescents. This is because, with the development of the times, consuming junk food become a lifestyle. Consuming junk food continuously will be bad for health. One of the bad effects is obesity. The research objective is that the researcher wants to know whether consuming junk food can affect obesity in high school adolescents. The method used is a literature review. Literature published from 2011 to 2021 in the form of a National Journal. Data obtained from the Google Scholar database with the keywords junk food, obesity, adolescents, consumption of junk food. The results obtained are 106 articles to be reviewed were accordance with the inclusion and exclusion criteria, namely 7 articles. The result of the review article show that there is a significant relationship between junk food consumption and the incidence of obesity in high school adolescents. Teens who consume junk food >3 times a day are at risk of experiencing obesity. This is because the content in junk food is high in fat and low in carbohydrates, so that fat settles in the body.